Implementasi Brand Placement melalui Media Film - Anisa Nur (UPT Publikasi Ilmiah UNISBA, 2023)
Abstract. The study entitled Implementation of Brand Image Through Movie Media: Semiotic Analysis Concerning to Brand BMW in Movie Mission: Impossible –Rogue Nation. This study aims to see the implementation of brand image through the medium of movie Mission: Impossible –Rogue Nation. The analytic process were using a model of Roland Barthes. The data were obtained from the movie Mission: Impossible –Rogue Nation produced by Paramount Pictures, Hollywood,United States. The Object of this study focused on the visual aspects of the movie Mission: Impossible –Rogue Nation. From these aspects it was concluded that BMW car has a high speed car image, capable of agile maneuver, reliable, high-tech, safe for the occupants, and also has the upper middle market. Researcher concluded that the movie Mission: Impossible –Rogue Nation successfully implemented the brand image of BMW